Dominant effect of ethanol in thermal destabilization of bovine serum albumin in the presence of sucrose. Issue 5 (2009) - Sathya Devi Sathya Devi, V. V.; Chidi Chidi, Obiora O. Obiora O.; Coleman Coleman, Denis Denis
Abstract : The thermal melting of bovine serum albumin (BSA) in the presence of excipients like ethanol and sucrose was studied by circular dichroism spectroscopy at physiological pH in phosphate buffered saline. Calculated apparent T m values were used to assess the thermal stability using two state fitted experimental curves. 0.5 M sucrose stabilized the BSA indicated by the increase in T m of ∼8°C when compared to the T m of the same solution measured in the absence of sucrose. Conversely, in the presence of varying concentrations of ethanol (2–20%), the protein was destabilized by a decrease of ∽3–10°C of T m . In the binary mixture of sucrose and ethanol, the T m values showed that ethanol dominantly destabilized BSA in the presence of sucrose, possibly by weakening the hydrophobic interactions in the protein.